(untitled) (Nepalese Journal of Cancer, 2026)
Background: Cancer is one of the most common diseases in children, leading to major challenges for caregivers and imposing a substantial caregiving burden. This burden can lead to negative health outcomes for the parents. The chronic nature of pediatric cancer places considerable demands on caregivers, severely impacting their well-being. Materials and Methods: A descriptive cross-sectional study design was used to assess the level of care burden among 100 family caregivers of children with cancer at pediatric oncology unit of B.P. Koirala Memorial Cancer Hospital, Chitwan, Nepal. Sample was selected through non-probability purposive sampling method and data were collected through modified Zarit Care Burden Interview Scale. Both descriptive and inferential statistics were used for data analysis with SPSS 22 version. Findings: Findings of the study revealed that 41% of the respondents had moderate level of care burden whereas 30% had low care burden, 28% had high care burden and only 1% had no care burden. There was significant association between level of care burden with the relationship with patient (p-value= 0.031) and the economic status of the family (p-value= 0.01). Conclusion: This study concludes that almost all of the family caregivers of children with cancer at BPKMCH had care burden. So, concerned health authorities need to provide family-centered measures and services to address caregiver burden ultimately improving their well-being and reduce the burden of caregivers.